Ganglioglioma of the Right Cerebrothalamus in a 7-Year-Old Quarter Horse Cross Gelding - Easton-Jones, Charlotte; Woolard, Kevin; Mohr, F. Charles; Roy, Melissa A.; Aleman, Monica (Frontiers in Veterinary Science, 2019)
Intracranial neoplasia in horses is rare compared to other species. Detailed information such as neurological, electroencephalographic, and histopathological examination of horses with intracranial neoplasia associated with seizures is scarce in the literature. Furthermore, ganglioglioma has not been reported in the horse. A 7-year-old Quarter horse cross Paint gelding was examined due to recurrent seizure-like episodes of one-year duration. The seizures had been increasing in frequency and length, occurring up to twenty times a day at the time of presentation. Neurological examination revealed intermittent obtundation and multiple left sided abnormalities consisting of facial and tongue hemiparesis, facial hyperesthesia and cervical hypoesthesia, proprioceptive deficits, thoracic limb hypermetria upon head elevation; and intermittent paroxysmal activity consistent with seizures. Cranial nerve reflexes were normal. Vocalization, conjugate vertical nystagmus, intermittent blindness, left sided head tilt and flexion of neck, and lack of response to environmental stimuli were observed during seizure activity. A right sided cerebrothalamic disease was suspected. An electroencephalogram confirmed seizure activity with main focus on the right side at the central, parietal, and occipital regions further supporting neuroanatomical localization. A ganglioglioma was identified in the right cerebrothalamic area, and other cranial parts of the brainstem based on immunohistochemical examination. To the authors’ knowledge this is the first report of intracranial ganglioglioma in the horse. This intracranial neoplasia should be added to the possible causes of intracranial masses and seizures in horses.